2021
DOI: 10.3389/frai.2021.613637
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Utilizing AI and NLP to Assist with Healthcare and Rehabilitation During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has profoundly affected healthcare systems and healthcare delivery worldwide. Policy makers are utilizing social distancing and isolation policies to reduce the risk of transmission and spread of COVID-19, while the research, development, and testing of antiviral treatments and vaccines are ongoing. As part of these isolation policies, in-person healthcare delivery has been reduced, or eliminated, to avoid the risk of COVID-19 infection in high-risk and vulnerable populations, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Furthermore, the religious congregations held in March also led to an increased number of cases. Therefore, social distancing must be encouraged to avoid the exponential dissemination of the disease (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the religious congregations held in March also led to an increased number of cases. Therefore, social distancing must be encouraged to avoid the exponential dissemination of the disease (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…According to NLP assumptions, people have the resources they need. In goal setting studies with NLP, the resources to be used while moving from the current situation to the desired situation were focused on, and awareness of their resources was created in patients [ [36] , [37] , [38] ]. With the help of NLP studies, patients found the courage and ability to cope with negative emotions, felt able to reach the goals they set, and the fear of COVID-19 decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, based on the principle that nurses use the patient's potential at the highest level while giving care, the principle of "people have the resources they need", one of the NLP assumptions, was used. NLP practices and goal-setting studies focused on the resources to be used to reach the desired state from the current situation, and awareness of their resources was created in patients (27)(28)(29). Thanks to NLP studies, patients found the courage and ability to cope with negative emotions, felt strong to reach the goals they set and decreased depression, anxiety, and stress.…”
Section: Discussionmentioning
confidence: 99%